Analisis Pembiayaan Pembangunan Dengan Penerbitan Surat Utang (Obligasi) Daerah Studi Kasus Pada Pemerintah Kota Bogor - Yanto, Edy Sudaryanto; Ramlan, Ramlan (Politeknik Negeri Ambon, 2024)
ABSTRACT Law Number 23 of 2014 concerning Regional Government mandates that local governments play an important role in determining the success or failure of creating self-reliance, but in practice, local governments encounter limitations in funding sources. Most of the districts and cities depend heavily on the transfer funds provided by the Central Government to the regions, be it Revenue Sharing Funds (DBH), General Allocation Funds (DAU), and Special Allocation Funds (DAK). Another source of income is from the limited Regional Original Revenue (PAD). Bogor City Government is one of the cities in West Java Province that has been given authority by the center to carry out regional autonomy. By handing over this authority, of course, the government hopes that the Bogor City government can explore the potential of the region to finance its development to reduce dependence on the central government. This study aims to analyze the feasibility of the Bogor City government issuing regional bonds (bonds) to finance its construction. This study used a descriptive qualitative research design with an analytical approach. From the analysis of financing through the issuance of regional bonds (bonds) which cover 3 (three) aspects namely legal, organizational, and financial, the Bogor City government has a score of 75% meaning that it is feasible to issue regional bonds (bonds). infrastructure.